4(3-u)=u+22+2u

Simple and best practice solution for 4(3-u)=u+22+2u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3-u)=u+22+2u equation:


Simplifying
4(3 + -1u) = u + 22 + 2u
(3 * 4 + -1u * 4) = u + 22 + 2u
(12 + -4u) = u + 22 + 2u

Reorder the terms:
12 + -4u = 22 + u + 2u

Combine like terms: u + 2u = 3u
12 + -4u = 22 + 3u

Solving
12 + -4u = 22 + 3u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-3u' to each side of the equation.
12 + -4u + -3u = 22 + 3u + -3u

Combine like terms: -4u + -3u = -7u
12 + -7u = 22 + 3u + -3u

Combine like terms: 3u + -3u = 0
12 + -7u = 22 + 0
12 + -7u = 22

Add '-12' to each side of the equation.
12 + -12 + -7u = 22 + -12

Combine like terms: 12 + -12 = 0
0 + -7u = 22 + -12
-7u = 22 + -12

Combine like terms: 22 + -12 = 10
-7u = 10

Divide each side by '-7'.
u = -1.428571429

Simplifying
u = -1.428571429

See similar equations:

| -8=-4n+8 | | 10+13y=1 | | 5(1-3a)=-85 | | y=177.46x-7e+06 | | 225y-80x=0 | | 108=3(-8+4x) | | 3x^2-12=-39 | | (X+4)(6)(x)=840 | | 4x^2-12x-12y+21=0 | | 6(6+3r)=108 | | 1/5x-18=2 | | 19.5-7.2=x | | 1/7x-3=6 | | 21+3c-7(2-3c)=4(c-5)+3c+27 | | 15(4n-4)=-60 | | 2(x-6)+2=9x-(7x+6)-4 | | 7/2x=3/x-5 | | 15=t/4-1 | | 6n+1=2n+1 | | 3v-8=7+2v-v | | 3(x+4)-5=4x-(2x+3) | | V-7=40 | | 2(x+4)-2=4x-(3x+2) | | 13x-9=-2(-4x-3) | | 3/4m=75 | | 20x-7=-3(-4x-3) | | 21+3c-7(2-3c)=4(c-5)3c+27 | | (8x^3)-(14y)+(12x)=0 | | 1/14b=-2.39 | | 0.37=ln(-2.5k) | | -0.994=ln(-2.5k) | | lnx=2.25 |

Equations solver categories